THE EFFECT OF PROFITABILITY, COMPANY SIZE, BOARD OF COMMISSIONERS, AND AUDIT COMMITTEE ON SUSTAINABILITY REPORT DISCLOSURE - Azzahra Ellba; Mohamad Auliyyaa Fauzi; Sasa S. Suratman; Endra Herdiansyah (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to examine the effect of profitability measures, company size, the board of commissioners, and the audit committee on the disclosure of the Sustainability Report. The population is all manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 – 2020. The sample was selected using a purposive sampling technique, resulting in 9 samples of manufacturing sector companies so the amount of data used was 36 data. This type of research method uses descriptive and verification methods, with a quantitative approach. The data used are secondary data obtained from www.idx.co.id, samahok.net, invesnesia.net, invesnesia.com, etc. along with literature books and economic journals. The result shows that Profitability, Company Size, Board of Commissioners, and Audit Committee simultaneously affect the Sustainability Report on Manufacturing Sector Companies listed on the Indonesia Stock Exchange (IDX).